Analysis of Physics Concept in the Making of Rotary Ice Cream - Singgih Bektiarso; I Ketut Mahardika; Diana Erista Ferli; Firlya Ika Septiviana; Farhan Arif Wahyudi; Wildan Adi Fadila (Peneliti.net, 2023)
Science which is a branch of cultural studies that seeks to understand how they interpret their nature can be called ethnoscience. Ethnoscience has several types of branches, one of which is ethnophysics. Ethnophysics is local wisdom associated with the concept of physics. This study used a qualitative method in the form of a literature survey. The aim of this research is to discover the physical concepts involved in the formation of rotating ice. There are 3 dominant concepts that exist in making rotary ice. Circular motion is a motion with a circular path. A change in the state of matter is a thermodynamic change that starts from one state of matter to another state of matter. In the experiment of making rotating ice cream, one of the mechanisms is to mix ice cubes with salt to lower the temperature of the ice to make it colder.